2016
DOI: 10.1166/jnn.2016.12158
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Pot Polyol Method for the Synthesis of Uniform Size Silver Nanowires

Abstract: This study reports the development of a facile and efficient one-pot polyol method for the synthesis of silver nanowires. The seed and growth of silver nanowires under different reaction conditions were characterized and measured. The pertinent variables such as temperature, time, concentration and capping agent were investigated. Moreover, the effect of seeding at two different stages-initial stage and secondary stage-was studied and discussed on the size control of silver nanowires. In particular, silver nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The formation of Ag NRs instead of longer Ag NWs may be due to the fact that the growth of Ag RBPs and the enlargement of diameters consumed more silver source, impeding the elongation of 1D Ag structures. Similar shortening mechanism was proved in other research on synthesizing Ag NRs . When more CQ was added, many byproducts of near-spherical silver particles were observed, as can be seen in Figure E, indicating that an overdose of CQ was unfavorable to the syntheses of Ag NRs and Ag RBPs.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The formation of Ag NRs instead of longer Ag NWs may be due to the fact that the growth of Ag RBPs and the enlargement of diameters consumed more silver source, impeding the elongation of 1D Ag structures. Similar shortening mechanism was proved in other research on synthesizing Ag NRs . When more CQ was added, many byproducts of near-spherical silver particles were observed, as can be seen in Figure E, indicating that an overdose of CQ was unfavorable to the syntheses of Ag NRs and Ag RBPs.…”
Section: Resultssupporting
confidence: 85%
“…It determines the diffusion coefficient, reduction kinetics, and also the reducibility of EG. In polyol synthesis, the length and diameter of Ag NWs are changed with temperature. ,, When CQ is added, the temperature also plays an important role in determining the morphology of products. SEM images of the obtained Ag nanostructures prepared at 100, 110, 120, and 150 °C and the corresponding yields of Ag NRs are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaili et al emphasized the importance of temperature in the range of 110-160°C as it determines the diffusion and reaction (nucleation and growth) rates. They showed that nanowire size decreases as the temperature increases due to increasing nucleation and growth [90]. Nghia et al used a microwave technique (800 W microwave oven equipped with a condenser) to synthesize AgNWs quickly with an irradiation time of 3.5 minutes and found that morphology depends strongly on the rate of heat [59].…”
Section: Effect Of Temperature In the Polyol Synthesis Of Agnwsmentioning
confidence: 99%
“…Kaili et al showed that PVP as a capping agent not only plays an essential role in preventing seed agglomeration but also helps heterogeneous growth of MTPs to wire shape. They investigated the effect of PVP molecular weight (55,000, 360,000, and 13,000,000) on the diameter and length of synthesized AgNWs and showed that while PVPs with large MW provide better product quality, very large MW (13,000,000) PVP is not suitable for synthesis of AgNWs with a high aspect ratio without nanoparticles as byproducts due to the viscous effect of the polymers [90].…”
Section: Effect Of Pvp Concentration and Molecular Weight As Amentioning
confidence: 99%